Pemahaman dan Keterlibatan Masyarakat Papua dalam Kargoisme - Roberth Ruland Marini (KHARISMATA: Jurnal Teologi Pantekosta, 2020)
The cargo cult is a pattern of belief and is considered to be the initial religion of the Papuan people, this is deeply embedded in the Papuan people. They have become Christians but also at certain times take part in ritual practices related to cargoism. The purpose of the study is to have a detailed understanding, also of the Sorido village community response, about cargoisme and also the consequences of what they experience as adherents of this belief. In the research analysis conducted was a qualitative analysis, with 16 participants answering 12 questions from 3 indicators sourced from one variable. Then the understanding and involvement of the Sorido village community in Biak Numfor Papua district on cargoisme has shown ontetic data that is in accordance with data calculation procedures, so it is known that 12.5% of participants trust cargoism and 87.5% of participants do not trust cargoism. And 87.5% of participants believed in the legend of Manarmakeri while 12.5% of the participants did not believe in the legend of Manarmakeri.AbstrakKultus kargo adalah pola kepercayaan dan diangap sebagai agama yang awal dari orang Papua, hal ini sangat tertanam di dalam diri orang Papua. Mereka telah manjadi Kristen tetapi juga masih pada waktu-waktu tertentu turut mengambil bagian dalam praktik-praktik ritual yang berhubungan dengan kargoisme. Tujuan penelitian agar ada pemahaman yang detail, juga mengetaui respon masyarakat kampung sorido, tentang kargoisme dan juga konsekuensi apa yang dialaminya sebagai penganut kepercayaan ini. Dalam penelitian analisis yang dilakukan adalah analisis kualitatif, dengan 16 partisipan menjawab 12 pertayaan dari 3 indikator yang bersumber dari satu variabel. Maka pemahaman dan keterlibatan masyarakat kampung Sorido kabupaten Biak Numfor Papua tentang kargoisme telah menunjukan data ontetik yang sesuai dengan prosedur perhitungan data, maka diketahui bahwa 12,5% partisipan mempercayai kargoisme dan 87,5% partisipan tidak mempercayai kargoisme. Dan 87,5% partisipan mempercayai legenda manarmakeri sedangkan 12,5% partisipan tidak mempercayai legenda manarmakeri.